DAKWAH PEMBERDAYAAN BERWAWASAN LINGKUNGAN UNTUK DAERAH KONFLIK DI PINGGIRAN HUTAN BALURAN BANYUPUTIH SITUBONDO - Samsul Arifin; Akhmad Zaini (As-Sidanah, 2019)
Access to social justice to obtain their rights for the outskirts of the forest in Baluran Situbondo is something difficult. One of them, because of years of conflict. The source of conflict in forest management occurs because of differences between the community and Baluran National Park. These differences, for example due to different perceptions, different knowledge, different values, different interests, and differences in recognition of ownership rights. One offer is the concept of collaborative management, a form of management that accommodates some of the interests of all stakeholders fairly and considers the value of each stakeholder as an equal entity in accordance with the applicable values ​​in order to achieve common goals. The focus of this research is empowering da'wah; namely the propaganda of advocacy, the preaching of economic empowerment, and the propagation of the religious field with environmental insight. Method: using a participatory rural appraisal (PRA) research approach. Results: First, the field of advocacy propaganda; which aims to make the public regain the power of management system, the power of ownership, and the power of unity system that is lost. Second, the mission of economic empowerment is environmentally sound; this program is to improve community welfare and increase community participation in the maintenance of the surrounding environment. Third, the religious field that aims to provide an understanding of environmental fiqh so that the community has a concern about the surrounding environment